2004
DOI: 10.1017/s0252921100011210
|View full text |Cite
|
Sign up to set email alerts
|

Nonradial Pulsations in Classical Cepheids of The Magellanic Clouds

Abstract: Abstract. We have performed systematic frequency analysis of the LMC Cepheids observed by OGLE project. Several new types of pulsation behaviour are identified, including triple-mode and amplitude-modulated double-mode pulsations. In ∼ 10% of the first overtone Cepheids we find low amplitude secondary periodicities corresponding to nonradial modes. This is the first evidence for excitation of nonradial oscillations in Classical Cepheid variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 3 publications
1
29
0
Order By: Relevance
“…5 we do not expect instability for l = 3 and 4. We can thus conclude that if low-degree p-modes with l ≤ 2 were necessary to explain the observations of Moskalik et al (2004), they cannot be attributed to a linear instability of these modes. Rather, other effects, such as, e.g., nonlinear mode coupling, have to be invoked for an explanation of their excitation.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…5 we do not expect instability for l = 3 and 4. We can thus conclude that if low-degree p-modes with l ≤ 2 were necessary to explain the observations of Moskalik et al (2004), they cannot be attributed to a linear instability of these modes. Rather, other effects, such as, e.g., nonlinear mode coupling, have to be invoked for an explanation of their excitation.…”
Section: Discussionmentioning
confidence: 82%
“…The stellar model whose parameters are thought to match the properties of the Cepheid observed by Moskalik et al (2004) is found to be unstable both with respect to radial and nonradial perturbations. Following modes up to l = 500, we find the following unstable modes: the fundamental p-mode for l = 0 and between 9 ≤ l ≤ 368, the first overtone for l = 0 and between 6 ≤ l ≤ 13, and the second overtone for l = 0, 5, and 6.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations